Layer-by-layer assembled film can serve as an enhanced reaction environment for Diels–Alder reaction - Fujisawa, Nanami; Ebara, Mitsuhiro (Frontiers in Chemistry, 2024)
Although the Diels–Alder reaction (DA) has garnered significant attention due to its numerous advantages, its long reaction time is a drawback. Herein, we investigated the effects of polarity difference on DA using Layer-by-Layer (LbL) films comprising polycationic polyallylamine hydrochloride and polyanionic poly (styrenesulfonic acid-co-furfuryl methacrylate) [poly (SS-co-FMA)] as the reaction environment. First, furan composition in poly (SS-co-FMA) was adjusted to be 19 mol% to achieve good water solubility and layer deposition. The successful formation of LbL films with 8 and 40 layers was confirmed by quartz crystal microbalance. The polarity within films and, consequently, the DA efficiency between furfuryl methacrylate and the maleimide in MAL-PEG2-NHS increased with an increasing number of layers up to 40 layers without requiring chemical modification on the reaction site of DA or any catalysts. Furthermore, we employed the LbL coating on the surface of magnetic nanoparticles (MNPs). The retro DA reaction (rDA) was successfully triggered by heating the MNPs by AC magnetic field. We believe that the proposed technology can serve as an enhanced DA reaction environment as well as temporal/spatial control of rDA in various applications.